Implementation of a perioperative management protocol for patients undergoing orthopedic surgery - Luiz Eduardo Imbelloni; Douglas M. P. Teixeira; Thatiany Monteiro Coelho; Danielly Gomes; Rafaela Lopes Braga; Geraldo Borges de Morais Filho; Alberto da Silva (Revista do Colégio Brasileiro de Cirurgiões)
OBJECTIVE: To evaluate the initial results after the implementation of perioperative protocol in patients over 60 years of age undergoing surgical treatment for femur fractures. METHODS: We conducted a prospective study of patients older than 60 years who were hospitalized with femur fracture. They were operated under spinal anesthesia and analgesia by lumbar plexus blockade. Data evaluation was performed before arrival in the operating room during surgery, in the post-anesthesia recovery room and in the ward the next morning of the operation. RESULTS: 105 patients underwent various types of surgical corrections of the femur. The hospital stay ranged from three to 86 days. Fasting ranged from 9h15min to 19h30mn. Hypotension occurred in 5.7%. The duration of motor blockade ranged from 1h45min to 5h30imn. Maltodextrin feeding ranged from 50min to 3h45min and the time spent in the post-anesthetic care unit ranged from 50 minutes to 4 hours. Onset of oral intake in the ward ranged from 4hto 8h15min. The duration of anesthesia ranged from 14 to 33 hours. No patient required a urinary catheter, nor was transferred to the ICU. All patients were able to be discharged on the first postoperative day. CONCLUSION: The use of a protocol to accelerate the postoperative period may reduce the fasting time, length of hospital stay and provide faster i discharge n elderly patients with femur fractures.